Penggunaan Media dan Metode Ajar Variatif dalam Menciptakan Pembelajaran Al Quran Hadist yang Dinamis - Mila Nurjamilah; Yanto Maulana Restu; Alisya Lutfiana; Neni Neni; Zahroh Tsamrotul Fauziah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Qur'an and Hadith education in the 21st-century learning era demands pedagogical transformation from conventional approaches toward more dynamic and meaningful learning. The integration of diverse teaching media and methods has become a crucial strategy in creating interactive, participatory learning experiences oriented toward holistic student competency development. This study aims to analyze the role of diverse teaching media and methods in creating dynamic Qur'an and Hadith learning at MAN 2 Tasikmalaya City. A qualitative descriptive approach was employed through observation, in-depth interviews, and documentation. Findings reveal that MAN 2 Tasikmalaya City has successfully implemented a combination of conventional media such as blackboards, textbooks, and student worksheets (LKS), integrated with lectures, question-and-answer sessions, group discussions, assignments, and modules that effectively fostered interactive and student-centered learning environments. The synergy of varied media and methods applied has proven effective in enhancing students' motivation, active participation, and deep understanding of Qur'anic verses and Hadith, while also shaping spiritual attitudes, discipline, and self-confidence. This study confirms that the varied learning practices at MAN 2 Tasikmalaya City represent a pedagogical strategy model relevant to the demands of 21st-century education and can serve as a practical reference for educators and other educational institutions in developing innovative and meaningful Qur'an and Hadith learning. Kata kunci: Learning media, varied methods, Qur'an and Hadith, dynamic learning, learning motivation